Pengaruh POC Campuran Kulit Kakao (Theobroma cacao L.) dan Kulit Pisang Kepok (Musa balbisiana) terhadap Pertumbuhan Tanaman Sawi (Brassica rapa) - Wahyudiansyah, Reyno Putra; Hanizar, Evi; Sugianto, Ferdy (Biocaster : Jurnal Kajian Biologi, 2025)
This study aimed to determine the effect of Liquid Organic Fertilizer (LOF) made from a mixture of cocoa husks (Theobroma cacao L.) and kepok banana peels (Musa balbisiana) on the growth of mustard greens (Brassica rapa). The study was conducted in Biting Village, Arjasa District, Jember Regency, using a Randomized Block Design (RBD) with five LFO concentration treatments (0%-40%) and eight replications. Observed parameters included plant height, leaf area, and number of leaves. Data analysis was performed using normality and homogeneity tests, followed by ANOVA or the Kruskal-Wallis test if the requirements were not met. The results showed that the 30% LFO treatment (P3) produced the highest number of leaves and was significantly different from the other treatments. Meanwhile, plant height and leaf area did not show significant differences. These findings indicate that the LFO mixture of cocoa husks and kepok banana peels has the potential as an alternative organic fertilizer that selectively supports vegetative plant growth, particularly in increasing leaf number, and also contributes to a sustainable agricultural system based on local waste.